First reported case of hydrocephalus in jointly diagnosed bacterial meningitis and a colloid cyst: how Ockham's razor became Hickam's dictum. (4th May 2022) - May, Gareth; Lammy, Simon; Kumar, Aditaya; Hegde, Ajay; St. George, Edward Jerome
Abstract: We report the first case in the literature of acute hydrocephalus due to a simultaneous diagnosis of bacterial (not asceptic) meningitis and a colloid cyst. Diagnosing disease is the cornerstone skill of a medical practitioner. Both education and experience allow for sharpening of this skill throughout years of medical practice. Disease is fraught with nuances and inconsistencies which can render an accurate diagnosis a difficult task. Medical practitioners can be guilty of cognitive biases such as Ockham's razor. We present the case of a patient with an initial diagnosis of obstructive hydrocephalus secondary to a colloid cyst. However, pneumococcal meningitis blunted Ockham's razor in favour of Hickam's dictum.